Comparative in vitro dissolution profiles of marketed Artemether–Lumefantrine adult-dose tablets in Kinshasa, Democratic Republic of the Congo - Bujo Dhimbe, Gloria; Ive Kitenge, Dadit; Tweny Baruti, Emile; Mankulu Kakumba, Jocelyn; Mbinze, Jérémie (Orapuh Journal, 2025)
Introduction Despite advances in clinical care, therapeutic strategies, and governmental interventions, malaria remains a significant public health concern—particularly in Africa, which consistently ranks highest in global morbidity and mortality reports from the World Health Organization. In the Democratic Republic of the Congo (DRC), malaria is one of the leading causes of medical consultations. This is largely due to the ineffectiveness of some antimalarial medications, which are often of substandard quality, contributing to therapeutic failures and the emergence of drug-resistant Plasmodium strains. Artemisinin derivatives are the mainstay of antimalarial therapy, with artemether–lumefantrine being the most commonly used oral formulation.Purpose This study aimed to evaluate the in vitro dissolution profiles of various artemether–lumefantrine brands available on the Congolese pharmaceutical market.Methods Fourteen brands of artemether–lumefantrine tablets at 80/480 mg and two at 20/120 mg dosage strengths were subjected to pharmaceutical quality control tests, including mass uniformity, friability, and disintegration. Qualitative and quantitative analyses were performed using high-performance liquid chromatography with diode-array detection (HPLC-DAD). Dissolution testing was conducted in 0.005 M HCl with 2% Myrj 52 at pH 1.2. Comparative dissolution profiles were assessed using similarity (f₂) and difference (f₁) factors.Results All samples complied with pharmaco-technical standards and demonstrated dissolution profiles comparable to the reference formulation (f₁ < 15; f₂ ≥ 50).Conclusion The artemether–lumefantrine generics available on the Kinshasa market exhibit similar in vitro dissolution characteristics to the reference product, supporting their potential interchangeability.